Congenital melanocytic nevi - Tannous, Zeina S. (2005)
Congenital melanocytic nevi occur in approximately 1% of newborns and are usually classified according to their size. Giant congenital melanocytic nevi are most simply defined as melanocytic nevi that are greater than 20 cm in largest dimension; whereas small congenital nevi are defined as melanocytic nevi less that 1.5 cm in largest dimension. Congenital nevi can exhibit distinctive histologic features that can help in differentiating them from common acquired nevi. Giant congenital melanocytic nevi are associated with an increased risk of the development of melanoma. On the other hand, there is evidence of an increased melanoma risk in patients with small congenital nevi. Nevertheless, the risk of malignant transformation in small congenital nevi and the lifetime melanoma risk in patients with small congenital nevi remain controversial. In large part due to inconsistency in the reported literature describing patients with congenital melanocytic nevi, the risk of melanoma in these patients remains unclear and consistent guidelines for clinical management do not exist. We review the literature and comment on the course of management for these patients at the Massachusetts General Hospital Pigmented Lesion Clinic.